Analisis Kualitas Minyak Trafo Menggunakan Data Dissolved Gas Analysis dan Water Content - Syakur, Abdul; Savitri, Fanny Rizka (Program Studi Teknik Elektro Universitas Khairun, 2018)
Transformer is a vital equipment in the power system. If the transformer is damage, can cause the electrical distribution to the consumer will be disrupted. Therefore, it needs special maintenance the performance of the transformer to avoid damage. One of them is the maintenance of the transformer oil. During the operation, the transformer oil will experience about thermal and electrical loading. Due to the load can cause dissolved gases in oil that could potentially lead to a breakdown in the transformer. It is needed monitoring against these gases. The other way to analyze the gas dissolved in oil is by using Dissolved Gas Analysis (DGA) test. The DGA will extract gases to know indications based on the interpretation of the data were performed. Therefore, damage of the transformer can be prevented. The results of DGA analysis on the transformer were discharge of energy and thermal fault obtained from data interpretation using Ratio Roger and Duval Triangle method. Also, it can be known that, the results of water content testing indicate oil condition are good (water content 9 ppm).KeywordsÃ¢â‚¬â€Dissolved Gas Analysis, Oil Transfomer, Water Content, Rasio Roger, Duval Triangle.